Penanaman Mangrove sebagai Upaya Mitigasi di Pesisir Pantai Lontar Banten - Siti Nurazizah (Universitas Negeri Semarang, 2025)
Mangroves are one of the plants that play an important role in terrestrial and coastal ecosystems in absorbing carbon dioxide and preventing abrasion. Mangrove nursery and planting activities carried out on the coast of Lontar Beach, Serang Regency, Banten, as an effort to mitigate and care for nature conservation, protect the coast from erosion, provide habitat for various species, and play a role in carbon absorption. The methods used include socialization to local communities about the importance of mangroves, then mangrove nurseries and planting are carried out at the location so that they succeed in increasing the area of planted mangroves. This activity is expected to have a long-term positive impact on coastal ecosystems. Therefore, this mangrove nursery and planting activity is not only beneficial in nature conservation, but also in education and empowerment of local communities, thus showing the importance of synergy between educational institutions and the community in environmental conservation efforts.